Meaning of justice proportional characteristics of hospital and patient relationship in hospital liability - Hari Pudjo Nugroho; Agus Yudha Hernoko; Otto Yudianto; Endang Prasetyawati (Technium Social Sciences Journal, 2022)
The type of research in this dissertation is normative juridical research. The emphasis of this research is on interpreting the meaning of the nature of hospital legal responsibility as mandated by Article 46 of Law 44/2009 on Hospitals and then developed by analyzing and reviewing various existing laws and regulations, to the ratio legis and the ontological basis for the birth of the article in the law. And the second is a conceptual approach. This research must look at the doctrines that develop in the science of law. In the conceptual approach must refer to the principles of law. Proportional justice in the relationship between the parties must be institutionalized in hospital bylaws consisting of corporate bylaws, medical staff bylaws, and clinical staff bylaws. The institutionalization of proportional justice in the relationship of the parties is to ensure a proportional distribution of obligations and rights for the parties. The legal relationship between hospitals and doctors, the institutionalization of proportional justice is created by the existence of work contracts and clinical contracts that are binding on both of them. In the work contract and clinical contract, even though it is only binding on the director who represents the hospital with a doctor, either employee doctor, attending physicist or independent contract, there must be a main component for consideration, namely patient safety. This employment contract and clinical contract binds hospitals and doctors but makes patient safety the main consideration.